In Vitro Evaluation of the Antagonism of Saprophyte and Endophytic Fungi Isolated from Groundnut (Arachis hypogaea) Against Soil-Transmitted Diseases Sclerotium rolfsii - Johanis Pelealu; Edwin de Queljoe; Lalu Wahyudi; Stella Deiby Umboh; Trina Tallei (JURNAL BIOS LOGOS, 2023)
Certain soil-borne diseases can have a detrimental effect on the quality and quantity of peanut production. One of the soil-borne diseases is Sclerotium rolfsii, a fungus that is the primary limiting factor in peanut plants. An alternative to controlling this fungus is to use saprophytic and endophytic fungi. The purpose of this study was to evaluate several saprophytic and endophytic fungi isolated from peanut plants in vitro as antagonistic agents against S. rolfsii. Isolation of saprophytic and endophytic fungi was carried out using the stratified dilution method. The fungal antagonism test was carried out using a non-factorial completely randomized design with 3 replications. The parameters observed in this study included the inhibiting zone, the diameter of the isolate colonies, the growth area, and the interaction of saprophytic and endophytic fungi with S. rolfsii. Five families and eight species of soil fungi were identified using macroscopic and microscopic identification techniques. The type of soil fungus has a large impact on the growth rate and inhibition area. Mucor hiemalis grew at the fastest rate, while Rhizopus oryzae had the largest inhibition zone.